A comparison of pRIFLE and AKIN criteria for acute kidney injury in pediatric intensive care unit patients - S., Srinivasa; V., Reshmavathi; G. S., Srividya (International Journal of Contemporary Pediatrics, 2016)
Background: ADQI group proposed the Risk, Injury, Failure, Loss of Kidney Function, and End-stage Kidney Disease (RIFLE) criteria for defining AKI. RIFLE criteria were later modified for paediatric patients and termed as Paediatric Risk, Injury, Failure, Loss, End Stage Renal Disease (pRIFLE). The Acute Kidney Injury Network (AKIN) group proposed modification to this system. While there are studies comparing RIFLE and AKIN criteria, they are limited to adult population. This study aims to compare between the pRIFLE and AKIN criteria in critically ill children admitted to Pediatric intensive care unit (PICU). Methods: All children admitted to PICU during December 2013 to May 2015 were included in the study. Serum creatinine was estimated on alternate days till death or discharge. The performance of pRIFLE and AKIN criteria for diagnosis and classification of AKI and its association with mortality was compared. Results: AKI occurred in 178 (26.1%) PICU patients through pRIFLE, risk in 108(15.9%), injury in 51 (7.5%) and failure in 19 (2.8%), while by AKIN criteria, AKI occurred in 248 (36.5%) patients, with 93 (37.5%) in Stage 1, 88(35.5%) in Stage 2 and 67(27 %) in Stage 3. Mortality rates were 13 (27.65%), 7 (14.89%), 12 (25.53%) and 15 (31.91%) for patients without AKI and at stages of Risk, Injury and Failure, respectively according to pRIFLE criteria. While for AKIN criteria, mortality rates were 7 (14.89%), 14 (29.78%), 15 (31.91%) and 11 (23.4%) for patients without AKI and at stages 1, 2 and 3 respectively. For pRIFLE criteria odds ratio (OR) for mortality was 0.92, 5.22 and 73.71 for Risk, Injury and Failure stage respectively. Results for AKIN criteria were, OR of 2.98, 3.60 and 3.15 for stage 1, 2 and 3 respectively. Conclusions: A higher incidence of AKI was diagnosed by AKIN criteria in comparison to pRIFLE criteria. Patients diagnosed with AKI had higher mortality. Both criteria had good association with mortality.